Pengaruh Media Sosial, Brand Image, Promosi, Live Streaming Dan Costumer Review Terhadap Keputusan Pembelian Pada Aplikasi Tiktokshop (Studi Kasus Masyarakat Kecamatan Pakis Kab Malang) - Bilqis, Nurul; Arifin, Rois; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the influence of social media, brand image, promotion, live streaming, and customer reviews on purchase decisions on the TikTok Shop application. With the increasing popularity of TikTok as a digital marketplace, this research focuses on the behavior of users in Pakis District, Malang Regency. A quantitative approach was used by distributing questionnaires to 105 respondents who had previously used TikTok Shop. Data were analyzed using validity tests, reliability tests, multiple linear regression, and classical assumption tests via SPSS. The results show that all independent variables—social media, brand image, promotion, live streaming, and customer reviews—have a significant positive effect on purchase decisions both partially and simultaneously. Among them, live streaming shows the strongest influence, indicating its growing importance in shaping consumer behavior. These findings suggest that effective utilization of digital features and social proof on TikTok Shop can enhance consumer trust and increase buying interest. This research contributes to digital marketing strategies by highlighting the key factors that influence purchasing decisions in the context of social commerce platforms. Keywords: TikTok Shop, purchase decision, social media, brand image, promotion,